VD_FINDINFO Arrêt / 2018 / 852 vom 3. Oktober 2018 - VD Tribunal cantonal (2018)
POUVOIR DE REPRÉSENTATION, VICE DE PROCÉDURE, DÉCISION D'IRRECEVABILITÉ | 61 let. b LPGA, 16 LPA-VD, 27 al. 4 LPA-VD, 27 al. 5 LPA-VD